Chitosan Composites for Bone Tissue Engineering—An Overview - Venkatesan, Jayachandran (Molecular Diversity Preservation International, 2010)
Bone contains considerable amounts of minerals and proteins. Hydroxyapatite [Ca(10)(PO(4))(6)(OH)(2)] is one of the most stable forms of calcium phosphate and it occurs in bones as major component (60 to 65%), along with other materials including collagen, chondroitin sulfate, keratin sulfate and lipids. In recent years, significant progress has been made in organ transplantation, surgical reconstruction and the use of artificial protheses to treat the loss or failure of an organ or bone tissue. Chitosan has played a major role in bone tissue engineering over the last two decades, being a natural polymer obtained from chitin, which forms a major component of crustacean exoskeleton. In recent years, considerable attention has been given to chitosan composite materials and their applications in the field of bone tissue engineering due to its minimal foreign body reactions, an intrinsic antibacterial nature, biocompatibility, biodegradability, and the ability to be molded into various geometries and forms such as porous structures, suitable for cell ingrowth and osteoconduction. The composite of chitosan including hydroxyapatite is very popular because of the biodegradability and biocompatibility in nature. Recently, grafted chitosan natural polymer with carbon nanotubes has been incorporated to increase the mechanical strength of these composites. Chitosan composites are thus emerging as potential materials for artificial bone and bone regeneration in tissue engineering. Herein, the preparation, mechanical properties, chemical interactions and in vitro activity of chitosan composites for bone tissue engineering will be discussed.